Molecular cloning and sequence of gilthead sea bream (Sparus aurata) alpha-skeletal actin: tissue and developmental expression - Moutou, K. A. (2014)
In the present study, the Sparus aurata -skeletal actin was cloned from a mixed larvae complementary DNA library. The clone isolated was 1523 bp long with an open reading frame of 1134 bp coding for a 377-amino acid protein. The deduced amino acid sequence of sea bream -actin is identical to Fugu -actin-1. The expression of -actin was initiated at the onset of segmentation. In adult fish, -actin is expressed predominantly in white and red muscle.